Linear Algebra : Key Ideas and Methods for a First Course - Tian, Haiyan ((Synthesis Lectures on Mathematics and Statistics))
Contiene: 1) Sistemas de ecuaciones lineales; 2) Transformaciones lineales; 3) Algebra matricial; 4) Determinantes; 5) Valores propios y vectores propios; 6) Ortogonalidad.